Modulation of matrix converters with improved performance - Rong, Run Jie. (2009)
Matrix converters are usually viewed as universal converters that can perform ac-ac energy conversion. At present, two types of matrix converters are commonly adopted, and it is the intention of this project to study them in details. After which, modulation schemes for controlling these converters are developed, which produce optimal performance for each of the matrix converters considered. The control scheme was tested in Matlab/Simulink simulation. Furthermore, a commutation problem is proposed and the solution for the problem is also presented in the report. The control scheme was tested in Matlab/Simulink simulation and a scale-down laboratory prototype. Both the simulation results and experimental results are presented in the last part of the report.